Melodi Savanna: Membangun Basic Listening Skill Melalui Musik Anak-Anak Di Madrasah Ibtidaiyah - Abdul Syahid; Syahrul Mubaroq; Tiara Nur Fatimah Almadani; Siti Nurrahmah; Muliana Setia Hapsari; Ayu Putriana; Muhamad Noor Fauzan (Universitas Maritim AMNI Semarang, 2024)
This community service initiative responds to issues related to listening skills and adopts a planned approach to achieve optimal learning goals. The focus of this intervention is on introducing an innovative method called